Apolipoprotein A1 reduces blood–spinal cord barrier leakage, improves astrocytic coverage, and enhances motor neuron survival to restore the neurovascular unit in ALS mice - Garbuzova-Davis, Svitlana; Manora, Larai; Borlongan, Cesario V. (Frontiers in Aging Neuroscience, 2026)
IntroductionAmyotrophic lateral sclerosis (ALS) is a progressive, age-related motor neuron degenerative disease with multiple causal factors. Dyslipidemia has been identified as an important pathological element. Impaired lipid protein metabolism manifests in ALS patients and in an ALS mouse model. Apolipoprotein components are the primary regulators of plasma lipid metabolism. Apolipoprotein A1 (ApoA1), a high-density lipoprotein, acts as an antioxidant and reduces inflammation, preventing blood vessel injury. However, the effects of ApoA1 upon the ALS-damaged endothelium in the CNS are unknown. The objective of the study was to determine the effect(s) of injecting ApoA1 into G93A SOD1 mice at the early symptomatic stage.MethodsA single dose of ApoA1 or media was systemically administered into 13-week-old G93A SOD1 male and female mice. Body weight and tests of motor function were evaluated weekly for 4 weeks post-injection. Permeability of spinal cord capillaries was determined by Evans blue (EB) fluorescent dye injected into mice at 17 weeks of age. Immunohistochemical analyses determined the statuses of glial cells and ApoA1 distributions in ALS mice cervical/lumbar spinal cords. Motor neurons in cervical/lumbar spinal cord ventral horns of ApoA1-treated and media-injected ALS mice were stained with cresyl violet for histological analyses.ResultsApoA1 injected into G93A SOD1 mice at the early symptomatic stage significantly benefited both male and female animals by (1) delaying behavioral disease progression; (2) reducing EB capillary leakage into spinal cord parenchyma; (3) lessening astrogliosis and microgliosis; (4) protein incorporation into capillary endothelium and motor neurons; and (5) improving survival of motor neurons in the spinal cord.ConclusionOur novel data showed that systemically administered ApoA1 benefited ALS mice of both sexes, likely by beneficial effects on damaged microvessels, possibly engendering restoration of neurovascular unit integrity. Moreover, an anti-inflammatory ApoA1 effect was demonstrated by the reduction of glial cell activation, potentially mitigating vascular injury. The results of our preclinical study suggest that ApoA1 may be a potential protein-mediated therapeutic for restoring vascular function. Our novel strategy may lead to future clinical trials, furthering our goal of effectively treating ALS patients.